Effect of Jet Nozzle Lip Momentum Loss on Circulation Control Airfoil Performance - Nishino, T; Shariff, K (2012)
Large eddy simulations of flow around a circulation control airfoil (using a Coanda jet blowing over its trailing surface) are performed to investigate the influence of jet nozzle lip thickness on airfoil performance. The airfoil geometry is only slightly changed from the authors' previous large eddy simulation study (Nishino, T., Hahn, S., and Shariff, K., "Large-Eddy Simulations of a Turbulent Coanda Jet on a Circulation Control Airfoil," Physics of Fluids, Vol. 22, No. 12, 2010. doi:10.1063/1.3526757) to study three different nozzle lip thickness cases; the geometry inside the nozzle is maintained as the same. The results show that the jet profile across the nozzle exit is insensitive to the nozzle lip thickness; however, the jet flow downstream of the nozzle exit decelerates more rapidly, and thus the circulation around the airfoil decreases as the nozzle lip thickness increases. It is subsequently shown that this effect is mostly cancelled out by adjusting the jet blowing rate in such a way that the difference of momentum loss arising from the nozzle lip is taken into account, demonstrating that the performance of a Coanda jet on a circulation control airfoil is determined not only by the jet momentum at the nozzle exit but also by the momentum loss behind the nozzle lip. These results suggest that it may be useful to define a new jet momentum coefficient that takes account of the momentum loss due to the nozzle lip, which can be roughly estimated once the velocity of the flow above the nozzle lip is known. Copyright © 2011 by the American Institute of Aeronautics and Astronautics, Inc. All rights reserved.